2002
DOI: 10.1093/jn/132.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia Is Highly Prevalent among Human Immunodeficiency Virus–Infected and Uninfected Infants in Uganda

Abstract: Although anemia is a common finding among human immunodeficiency (HIV)-infected infants in sub-Saharan Africa, the factors contributing to the pathogenesis of anemia have not been well characterized. We sought to characterize the relative contribution of iron deficiency and chronic disease to the anemia among infants. Hemoglobin, ferritin, erythropoietin, tumor necrosis factor-alpha (TNF-alpha), neopterin, CD4(+) lymphocyte count and plasma HIV load were measured in 165 HIV-infected and 39 uninfected 9-mo-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
35
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
6
35
1
Order By: Relevance
“…31 Iron deficiency is highly prevalent (18.0-44.3%) in developing countries, 3,29 but not in this study. The high prevalences of IDA in other studies might be the result of the inclusion of children with poorer nutritional status and more severe clinical stage of HIV.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…31 Iron deficiency is highly prevalent (18.0-44.3%) in developing countries, 3,29 but not in this study. The high prevalences of IDA in other studies might be the result of the inclusion of children with poorer nutritional status and more severe clinical stage of HIV.…”
Section: Discussioncontrasting
confidence: 57%
“…[27][28][29][30] In this study, we found that half of ARV-naive Asian children without advanced HIV had anemia. Most anemic children had a mild degree of anemia.…”
Section: Discussionmentioning
confidence: 60%
“…Anemia is common among children with HIV infection [14,47] and has been established as an independent marker for increased disease progression and death in both adults [23,45] and children [6,10]. An extensive national-level survey of the general Indian population revealed that 45% and 40% of children aged 6 months-3 years were stunted and underweight, respectively, and that 79% had anemia, of which iron deficiency was believed to be the leading cause [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although the anemia of infection, a subset of the anemia of chronic disease (Means, 2000), may account for a large part of the anemia found in pulmonary tuberculosis, iron deficiency (Semba & Gray, 2001;Yip, 2001;Moyle, 2002), poor antioxidant status (Semba & Gray, 2001), and vitamin A deficiency (Moore, 1999;Semba & Bloem, 2002) may potentially contribute to the anemia. A blunted response of erythropoietin to anemia may occur in the anemia of infection (Means, 2000) and has been described in HIVinfected adults (Spivak et al, 1989;Camocho et al, 1992) and children (Totin et al, 2002). Interleukin-6 (IL-6), a proinflammatory cytokine, is a marker for the severity of infection (Wakefield et al, 1998) and has been shown to modulate the anemia of chronic disease (Feelders et al, 1998).…”
Section: Introductionmentioning
confidence: 99%